Localisation of the DmCdc45 DNA replication factor in the mitotic cycle and during chorion gene amplification. - Loebel, D.; Huikeshoven, H.; Cotterill, S. (Nucleic Acids Research, 2000)
The cdc45 protein was originally identified in Saccharomyces cerevisiae and shown to be essential for initiation of eukaryotic DNA replication. Subsequent isolation and characterisation of the corresponding genes from fission yeast, Xenopus and mammals also support a replication role for the protein in these species. They further suggest that during the course of its function cdc45 interacts with a number of other replication proteins, including minichromosome maintenance proteins, the origin recognition complex and DNA polymerase alpha. We have cloned the gene coding for cdc45 protein from Drosophila melanogaster. We have analysed the expression pattern of the cdc45 protein throughout the cell cycle and the life cycle using a combination of indirect immunofluorescence and subcellular fractionation. Our data show that cellular localisation and developmental regulation of the protein is consistent with a role in DNA replication. DmCdc45 is predominantly expressed in proliferating cells. In addition, its subcellular location is nuclear during interphase and the protein shows association with chromatin. The chromatin-associated form of the protein shows a post-translational modification, which may be involved in control of the action of the protein. DmCdc45 shows interactions with mcm proteins, however, the interactions detected show some specificity, perhaps suggesting a preferential association with particular mcm proteins. In addition we show that a stoichiometric mcm interaction may not be obligatory for the function of cdc45 in follicle cell replication, because, unlike the mcm proteins, DmCdc45 localises to the chorion amplification foci in the follicle cells of the ovary.